The effects of prolonged mechanical ventilation on the alpha-adrenergic responses of costal diaphragm arterioles - Horn, Andrew Gary (Kansas State University, 2019)
Introduction: Mechanical ventilation (MV) is a life-saving intervention employed in Intensive Care Units worldwide. Previous work has shown a substantial time-dependent reduction in diaphragmatic blood flow and O₂ delivery with MV, likely contributing to diaphragm fatigue and weaning difficulties. However, the precise mechanism(s) responsible for these alterations in blood flow are unknown. Given the reduction in diaphragmatic blood flow with prolonged MV, we tested the hypothesis that prolonged MV (e.g. 6 hours) enhances diaphragm arteriole contractile responses to alpha-adrenergic agonists with no change in sensitivity. Methods: Female Sprague Dawley rats (5-8 mo) were randomly divided into spontaneous breathing (SB, n = 9) and prolonged MV (6 h MV, n = 6) groups. Following SB and 6 h MV, diaphragm arterioles (~200 [mu]m diameter, ~2 mm in length) were isolated, cannulated, and pressurized to develop spontaneous tone. Thereafter, contractile responses to cumulative doses of non-selective [alpha]-adrenergic receptor agonist, norepinephrine (NE), and [alpha]₁-adrenergic receptor specific agonist phenylephrine (PE) (10⁻⁹ to 10⁻⁴M) were determined. Results and Conclusion: Prolonged MV did not alter maximal vasoconstrictor responses to NE but reduced PE-induced vasoconstriction (SB, 37.3 ± 6.7 vs. MV, 19.0 ± 1.9%; p≤0.05). Sensitivity (EC₅₀; concentration of a drug needed to elicit half-maximal response) was significantly reduced following prolonged MV, in response to NE (p≤0.05) and PE (p≤0.05). Following 6 h of MV, the reduction in a–adrenergic responsiveness occurs through both endothelial-dependent and –independent mechanisms, and likely contributes to the severe reductions in diaphragmatic blood flow and O₂ delivery during MV. Future studies are warranted, investigating responses to other vasoactive mediators such as Angiotensin-II and Endothelin-1, as well as potential alterations in vascular mechanical and material properties, with MV.
Keywords: Mechanical ventilation; Diaphragm; Arterioles; Alpha-adrenergic